LEGAL (DE) SUPPORT TO CONSCIENTIOUS OBJETION (ESMAT Magazine, 2021)
The purpose of this article is to analyze the conscientious objection. The right to freedom of conscience and the guarantee of its exercise through conscientious objection are the subject of many controversies in Brazilian and foreign doctrine and case law, deserving the attention of jurists and the general population. The aim of the present work is the analysis of such phenomenon, which manifests itself in the opposition to the fulfillment of norms orlegal rules for reasons of conscience. Such reflection performs through the deductive method and theoretical research. At the end, the conclusion was that there are several bills addressing the theme of conscientious objection, however, without legislative technique and often in a prejudiced way.
Keywords: objection, conscience, freedom, fundamental rights.